Additive manufactured magnetic sheet, lamination stack and electric machine
By introducing material concave lines into the magnetic sheet and passing through the boundary lines between the material components, the high mechanical stress problems generated by the two-component magnetic sheet during cooling are solved, and the strength and magnetic properties of the magnetic sheet are improved.
Patent Information
- Application Number
- CN202380067535.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-23
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-29
AI Technical Summary
After sintering, due to the different thermal expansion coefficients of the material components, existing two-component magnetic sheets produce higher mechanical stress during cooling, which may lead to warping, cracks or deterioration of mechanical and magnetic properties.
In the magnetic sheet, the material concave lines are introduced through the boundary line between the material components, with an extension angle α between 45° and 135°, reducing thermal stress through such a structured transition zone and increasing the strength of the magnetic sheet.
By introducing material concave lines, the average stress state in the magnetic sheet is reduced, the mechanical strength and magnetic properties of the magnetic sheet are improved, the internal stress is reduced, and warping and cracking are avoided.
Smart Images

Figure CN119908062A_ABST
Abstract
Description
[0001] The invention relates to an additively manufactured magnetic lamination according to claim 1 , a laminated core according to claim 13 , and a method for producing an electric machine according to claim 15 .
[0002] Screen printing or template printing is a new method for producing magnetic sheets for electric motors. In this process, a printing paste is printed onto a substrate with the aid of a template, in which the open areas can also be provided with a screen. This involves template printing or screen printing, wherein template printing is a general term for screen printing. In addition to solvents and / or adhesives, the printing paste also contains metal powders, which have a functional influence on subsequent components. The green body is manufactured by screen printing technology, and after further heat treatment, the green body is usually first debonded and then sintered at a higher temperature, wherein the metal powder particles sinter to each other to form a structured sheet, i.e. a magnetic sheet.
[0003] In order to achieve higher mechanical strength, especially when the motor rotor rotates at high speed, the manufacturability of two-component magnetic sheets is becoming increasingly important. An example of this is described in EP 3723249 A1. EP 3 629 453 A1, EP 3 932 591 A1 and EP 3 725 435 A1 should also be mentioned here. The fundamental problem in the manufacture of such two-component magnetic sheets using a stencil printing process is that if different materials have good magnetic properties on the one hand and high strength on the other hand, these different materials usually have different thermal expansion coefficients. For example, the expansion coefficient of high-strength steel, which is a component used to form the mechanical strength of the magnetic sheet, is 16×10 -6 K -1 Another soft magnetic material has a magnetic field strength of 10-12×10 -6 K -1 When these different material components or material pairs in the green body are sintered together to form a magnetic sheet, due to the different thermal expansion coefficients, high mechanical stress is generated in the connection area or seam area between these material components, especially when cooling from the sintering temperature to room temperature. This may cause warping, cracks in the magnetic sheet, or mechanical stress on the whole, which significantly deteriorates the mechanical properties or magnetic properties.
[0004] The technical problem to be solved by the present invention is to provide a magnetic sheet and thereby a laminated core and an electric machine, which have higher strength and lower internal stress compared to the prior art when at least two material components are used in the magnetic sheet.
[0005] This object is achieved by a magnet lamination according to claim 1 , a laminated core according to claim 13 and an electric machine according to claim 15 .
[0006] The rotationally symmetrical magnetic sheet of the additively manufactured lamination stack for an electric motor according to the present invention has the following characteristics. There are at least two material components that are separated from each other in a planar extension. This is a first material component and a second material component. The two material components meet at an interface, which forms a boundary line when observed perpendicular to the plane of the sheet. Material grooves are introduced into the magnetic sheet, which extend from the first material component through the boundary line to the second material component. An extension angle is defined for the extension direction of the material grooves, which is referenced to the tangent of the boundary line, specifically the tangent at the point where the material grooves intersect the boundary line. The angle α is at least 45° and at most 135° relative to the tangent.
[0007] As mentioned at the beginning, the greatest stresses in two-component magnet sheets due to the different expansion coefficients of the components occur especially during the cooling process from the sintering stage. Of course, due to the increase in operating temperature, thermal stresses are also generated during the operation of the motor, but the highest thermal stresses are caused by the cooling process during manufacturing, i.e., when the magnet sheets are sintered. In order to reduce or even avoid such thermal stresses, the material grooves are introduced into the magnet sheets so that they extend through the boundary lines between the individual material components.
[0008] This results in regions in which, at the initially defined stress state, the actual strain, i.e. the absolute strain, which is caused by the temperature change or the cooling process due to the different coefficients of thermal expansion, is greater or less due to the different coefficients of expansion. Thus, the residual mean stress state can be reduced on average compared to an unstructured transition region. Thus, the effect of this structuring achieved by means of a material concave transition region between the material components can be similar to a spring element in mechanics.
[0009] The material concavity preferably extends almost perpendicularly to the tangent at the intersection of the material concavity and the boundary line. However, depending on the extension of the boundary line, deviations from this extension perpendicular to the tangent may be expedient. These deviations are 45° to 135° relative to the extension perpendicular to the tangent, i.e., at 90° to the tangent.
[0010] The term "material concave line" is generally understood to mean a line with a high aspect ratio, preferably greater than 5, which does not necessarily have to be an accurately drawn line. A circular or elliptical extension or a meandering shape along its extension line when crossing a boundary line may also be suitable. The cross section of the material concave line does not necessarily have to be exactly rectangular. A circular or elongated rectangular cross section or a rectangular cross section that is wider in terms of area ratio may also be suitable. It should be noted that magnetic sheets with a thickness of usually between 100 and 200 μm must originally make concessions in terms of accuracy due to process technology tolerances when representing a specified cross section or a certain length and width of the line.
[0011] The material depressions can be produced completely by punching out the magnet sheet, but can also be scored, milled or deformed depressions.
[0012] The exact number of material grooves, density along the boundary line, length, orientation relative to the tangent to the boundary line, and cross-sectional structuring depend to a large extent on the material composition used and therefore also on the expansion coefficient of the material composition. These parameters are also significantly affected by the layout, i.e. the design of the magnetic sheet. It has been proven to be suitable in a number of calculations that the material grooves have a length of 1 mm to 10 mm. The depth of the material grooves is suitable, as described, between complete punching penetration and 10% indentation, so that this size depends in particular to a large extent on the described conditions, layout and material composition. The distance between the material grooves or material ridges is preferably less than or equal to their length. For example, if the length is 5 mm, the distance is preferably 0.5 mm to 5 mm.
[0013] In order to accurately determine the dimensions of the corresponding magnetic sheets used, when designing the magnetic sheets, the number, density and design of the material grooves at the boundary lines are accurately determined with the help of the finite element method, knowing the thermal expansion coefficients of the material components used and knowing the magnetically and mechanically optimized layout, so that these material grooves can be introduced accordingly during the manufacturing process based on finite element calculations.
[0014] The positive effect of the material concavity and the fact that the absolute expansion rate of the material along this weakened area is lower, so that thermal stresses are reduced or completely eliminated, is also accompanied by a negative effect, namely the pure weakening of the material in the area of the boundary line. The introduction of the material concavity is therefore a compromise between the increase in strength by reducing thermal stresses and the simultaneous weakening of the material. Nevertheless, the negative effect of the material weakening is significantly smaller than the positive effect of the stress reduction. This compromise represents an optimization problem that can also be solved by the described method using the finite element method.
[0015] Another method of specifically counteracting material weakening is to simultaneously raise the material or introduce material raising lines which are oriented similarly to the material depressions. They also pass through the boundary line and have the same angle α to the tangent, which is called α' and is 45° to 135°.
[0016] These material ridges can be produced, for example, by material application or by deformation stamping on the reverse side of the magnetic disc, and these material ridges will still be described when the individual magnetic discs are assembled into an integral lamination stack. It is appropriate that the material ridges of the magnetic disc engage in the material grooves of the subsequent magnetic discs of the lamination stack. The weakening of the material at this position is thereby compensated, and the influence of the material grooves on the thermal expansion coefficient still exists. In order to prevent such magnetic discs from warping or deforming during sintering and operation, it is advantageous to design the magnetic discs rotationally symmetrically relative to the center axis of the magnetic disc, especially the rotationally symmetrical design of the transition area along the boundary line relative to the center axis of the magnetic disc. The center axis of the magnetic disc also coincides with the rotation axis of the rotor, which contains the subsequent lamination stack. Rotational symmetry is understood here as the point symmetry of the radius relative to the center point, and for the rotor, it is understood as the point symmetry of the intersection point relative to the center axis.
[0017] It is also advantageous if the boundary line is formed from one of the material components so that this material component forms an undercut in the other material component. However, such an undercut should only be achieved by the one material component entering the respective other material component and should not be done alternately. It is also expedient here for the material component with a higher coefficient of thermal expansion to form an undercut in the material component with a lower coefficient of thermal expansion, since this results in a tensioning process between the components. If there are undercuts on both sides, these tensioning processes would interfere with each other and could cause further stresses.
[0018] As mentioned above, the magnetic sheet comprises at least two different material components, which differ in particular in terms of mechanical properties and magnetic properties. In this way, the required technical properties can be studied in a targeted manner in a certain area of the magnetic sheet. Therefore, the first material component has an iron alloy with an austenitic structure of at least 25% by volume. This austenitic structure, which can be achieved in particular using high-alloy steel, has very high strength, in particular tensile strength and bending strength.
[0019] The second material component, on the other hand, comprises an iron alloy having at least 95% by weight, in particular at least 97% by weight, of iron. The second material component is preferably pure iron, which has very good magnetic properties, in particular soft magnetic properties, and can be remagnetized very well in the form of hysteresis. It should be noted here that the data relating to the austenitic structure are given in volume %, while the alloy data are given in weight %. This is because in micrographs, the structure can be more clearly represented microscopically in volume %, while the alloy components are represented in weight %, which is common in technology and represents clear manufacturing instructions for the composition of the alloy.
[0020] The second material component having very good soft magnetic properties also has a preferred ferrite and / or martensite structure.
[0021] The first material component having a high mechanical strength and ensuring the strength of the entire magnetic disk during rotational movement is also preferably an iron-chromium-nickel alloy. The iron-chromium-nickel alloy also preferably has a chromium content of preferably between 22% by weight and 28% by weight, in particular between 24% by weight and 26% by weight. In addition, the nickel content of the iron-chromium-nickel alloy is between 4% by weight and 10% by weight, in particular between 6% by weight and 8% by weight.
[0022] Another component of the invention is a lamination stack according to claim 13. Such a lamination stack for a rotor of an electric machine comprises a plurality of magnetic sheets according to the preceding claims. It has been found to be particularly suitable here if the magnetic sheets of the lamination stack are stacked in such a way that the material depressions of one magnetic sheet are filled by the material elevations of the second magnetic sheet. This increases the filling factor of the effective magnetic material in the lamination stack, in particular the filling factor of the material of the second material component, and reduces the weakening of the magnetic sheets due to the introduction of material depressions at the boundary lines.
[0023] Another component of the invention is an electric machine comprising a laminated core according to claim 13 or 14. By using high-strength magnetic sheets according to the above claims, such an electric machine has the advantage that the magnetic properties of such magnetic sheets or the laminated core produced therefrom are enhanced. The electric machine can be, in particular, an electric motor or a generator.
[0024] Other designs and other features of the present invention are described in detail according to the following drawings. This is a purely schematic view and does not constitute a limitation of the scope of protection. Features with the same name but in different designs are respectively provided with the same reference numerals.
[0025] In the attached picture:
[0026] Figure 1 shows a 3D exploded view of a typical electric motor,
[0027] Figure 2A lamination stack comprising a plurality of two-component magnetic sheets is shown,
[0028] Figure 3 Shown with Figure 2 A top view of a two-component magnetic sheet with a similar design as in,
[0029] Figure 4a Shows Figure 3 The enlarged local area,
[0030] Figure 4b An enlarged view of the dashed box IVb is shown
[0031] Figure 4c shows a schematic cross-sectional view along line IVc,
[0032] Figure 5a , 5b Shown with Figure 4b , 4c A similar view, but with an alternative design,
[0033] Figure 6a , 6b An alternative design scheme of FIG. 5 is shown,
[0034] Figure 7a , 7b FIG. 6 shows an alternative embodiment with an undercut between the first and second material components.
[0035] Figure 8 Schematic diagram showing possible stacking sequences of cross sections of different magnet sheets,
[0036] FIG. 9 shows a schematic diagram of a manufacturing method for manufacturing a two-component magnetic sheet.
[0037] In order to better classify the magnetic sheets 2, first Figure 1 2 shows an exploded view of an electric machine 6. The electric machine comprises a rotor 24 and a stator 25 surrounded by a housing 26. The electric machine 6 can be an electric motor or a generator. The rotor 24 in turn comprises Figure 1 In the lamination stack 4 which is not explicitly shown, the electrically conductive wire is arranged in a defined manner as a coil around the lamination stack 4 . Figure 2 Such a laminated core 4 is shown as an example. Figure 2 The laminated core 4 has a stacked structure of a plurality of magnet sheets 2 , wherein the layout of the magnet sheets 2 is designed such that the magnet sheets form corresponding recesses and grooves for conductor windings.
[0038] exist Figure 2The magnetic sheets 2 stacked into a lamination group 4 have two material components 8 and 10. The first material component 8 is designed to preferably include a high-alloy, high-strength steel, preferably an iron-chromium-nickel alloy first material component 8, which plays a decisive role in the strength of the magnetic sheet 2. The second material component 10 has soft magnetic properties in particular and exhibits particularly good re-magnetizability. Ideally, the second material component consists of pure iron, which has particularly good soft magnetic properties. The iron content of the second material component 10 is preferably at least 97%, and the microstructure of the second material component 10 is generally preferably a ferrite structure or a martensite structure. The structure of the first material component 8 preferably has an austenite structure.
[0039] Furthermore, in the uppermost magnetic sheet 2 of the lamination stack 4 , a material concave line 16 is shown along the boundary line 14 between the first material component 8 and the second material component 10 , which will be discussed in detail in the following figures.
[0040] Figure 3 Shown with Figure 2 A top view of a magnetic sheet 2 similar to the magnetic sheet shown in the lamination stack 4 in FIG. Here, too, there are two material components 8 and 10, the first material component 8 having a higher mechanical strength and the second material component 10 having a good soft magnetic strength. Figure 3 The layout of disk 2 in Figure 2 The layout of the magnetic disk in FIG. 1 is different in that six regions with a soft magnetic material component 10 are provided instead of four. Figure 2 and Figure 3 The two magnetic sheets 2 in the embodiment have in common a rotational symmetry with respect to the central axis 22, which is also consistent with the rotational symmetry according to Figure 1 The rotor axes of the motors coincide.
[0041] Figure 4a Shows Figure 3 An enlarged view of a local area IVa in FIG. An exemplary material concave line 16 is shown here, which is Figure 4b Further explanation is given in the further enlarged local area. Figure 4c It also shows that along Figure 4b Cross section along line IVc.
[0042] In observing Figure 4cIn the cross section shown, the first material component 8 and the second material component 10 meet at the interface 12. In practice, due to tolerances and conditions in the process technology, the interface 12 is usually not an absolutely discrete interface 12, but a transition zone in which the material undergoes a diffusion process due to the sintering process and thus forms the transition zone. However, in the top view of the magnetic sheet, a boundary line 14 is shown, which extends along the interface 12 between the two material components 8 and 10. These boundary lines 14 are penetrated by material grooves 16, which extend from the first material component 8 through the boundary lines 14 to the second material component 10. In order to define the extension direction of the boundary line 16, a tangent 18 is first defined, which is located at the point where the material groove 16 intersects the boundary line 14. The extension direction of the material groove 16 is usually perpendicular to the tangent 18. However, as Figure 4a As shown, the material depression can also form an angle α of 45° to 135° with the tangent line 18. However, the angle α relative to the tangent line 18 is preferably 85° to 95°.
[0043] The effects of material concave lines and their design solutions are described below. Figure 4b A plurality of material indentations 16 are shown, which also extend substantially perpendicularly to the tangent line 18, so that the angle α is approximately 90°. Figure 4b The material concave line 16 can be a punched through portion of the magnetic sheet 2, which can be Figure 4c Along the Figure 4b On the other hand, the material concave line 16 can also be a local groove, which is also formed by Figure 4c Shown.
[0044] The manufacturing technology of the magnetic sheet 2 with two material components 8 and 10 will be described in detail according to FIG. 9. It is described here that the magnetic sheet 2 is a sintered metal sheet with two components 8, 10. When the sintered two-component sheet 2 cools, thermomechanical stresses are generated in the interface 12 along the boundary line 14 due to the different thermal expansion coefficients of the two material components 8, 10. Due to the introduction of the material concave line, the material density at the boundary line 14 is lower, which also leads to different absolute expansion rates of the material in this area. The generated thermomechanical stresses are thus at least partially compensated by the material concave line 16 similar to the spring element.
[0045] according to Figure 4b and 4c The material groove 16 is designed here as a line with a rectangular cross section. This is a simplified illustration; in practice, the material groove 16 can be designed differently depending on the expansion coefficients of the individual material components 8, 10 and the layout of the magnetic disk 2. In order to accurately calculate the shape and extension direction of the material groove 16 as well as the length and depth, a calculation method implemented by finite element analysis is preferably used, which is based on different parameters, namely the expansion coefficient and the layout of the magnetic disk 2.
[0046] The two material components 8, 10 have different technical properties. The first material component comprises in particular a high-alloy chromium-nickel steel, which preferably comprises an austenite structure of more than 25% by volume. The chromium content is, for example, 25% by weight and the nickel content is 7% by weight. This alloy is a very high-strength stainless steel alloy. Figure 2 and Figure 3 It can be seen that the first material component is arranged centrally inside the magnet disk 2 , so that when the rotor 24 performs a rotational movement, the first material component is subjected to the highest tensile load acting on the magnet disk 2 or the laminated core 4 formed thereby.
[0047] The material properties of the second material component 10 are particularly focused on magnetic properties. Ideally, the material of the second material component 10 is made of pure iron and has a ferrite structure and a martensite structure. Pure iron has the best soft magnetic properties and is easy to repolarize in this regard. This is of great significance for AC motors or generators.
[0048] Although the two different material components 8, 10 are usually composed of iron alloys, their electrical expansion coefficients still have certain differences. Depending on the alloy composition, the expansion coefficient between the various iron alloys can be, for example, 10×10 -6 K -1 Up to 20×10 -6 K -1 In addition, a temperature increase from room temperature to 200°C (which may be the operating temperature of a high-performance motor running at high speed) may also cause the expansion coefficient to change by 10×10 -6 K -1 However, these differences between the individual expansion coefficients, which depend on the material composition and also on the operating temperature range of the machine, lead to significant thermomechanical stresses at the interface 12 or along the boundary line 14 between the individual material components 8 and 10. As already mentioned, further high thermomechanical stresses arise during cooling from the desired sintering temperature.
[0049] Figures 5 and 6 show the Figure 4b and Figure 4c Similar views. Figure 5a and 6a A top view of a corresponding partial region along the boundary line 14 between the two material components 8, 10 is shown again. Also shown is a material elevation line 20, which can also be formed according to Figure 5b and Figure 6b The material elevations 20 can be used to compensate for the material weakening caused by the material depressions 16 . Figure 8 The possibility of compensation is explained.
[0050] Figure 8 The stacking sequence of the magnetic sheets 2 is shown, wherein the material ridges 20 and the material grooves 16 complement each other in the following manner, so that when the lamination stack 4 is stacked, the material ridges 20 of the first magnetic sheet 2 are embedded in the material grooves 16 of the second magnetic sheet 2. In this way, the filling degree of the lamination stack 4 is increased and the reduction in mechanical strength that may be caused by the material grooves 16 is compensated. Figures 5 and 6 show other possible cross-sections of the material grooves 16, which are marked as 16' here. The schematic illustration here involves circular recesses, which are Figure 4c An alternative form of the rectangular recess is shown. The type of material to be chosen for the type of recess 16 depends on an optimization calculation, which can be carried out, for example, by means of the finite element method already described.
[0051] FIG. 7 shows a view similar to FIGS. 4 to 6 , wherein in addition to the material concave lines 16, undercuts 28 of the boundary line 14 are shown. These undercuts extend from the first material component 8 having the undercuts 28 into the second material component 10. The undercuts 28 are a particularly advantageous measure if the material component of the two material components 8 , 10 having the greater coefficient of thermal expansion forms the undercuts 28. This measure results in a stretching effect on the respective other material component 8 , 10 when the material component forming the undercuts 28 contracts. Undercuts on both sides, i.e. alternating undercuts from one material component 8 , 10 to the other, are not suitable for counteracting the stretching effect.
[0052] The manufacturing method of the above-mentioned corresponding magnetic sheet 2 is also explained according to FIG. 9. The magnetic sheet 2 is preferably manufactured using a template printing process, wherein a template 30 is arranged on a substrate 34, and a printing paste not shown in FIG. 9 is printed on the substrate by means of a scraper 32. The template 30 has an opening through which the printing paste is pressed onto the substrate. The opening of the template 30 is preferably equipped with a screen, so that this process is also often referred to as screen printing. When manufacturing a two-component sheet, this printing is performed twice with different templates, so that Figure 9b As shown, a two-component green body 36 having a first material component 8 and a second material component 10 is produced on a substrate 34. The green body is particularly freed of organic solvents and binders in the printing paste in a debinding furnace 38, where they are thermally decomposed or vaporized. The green body 36 produced in this way is placed in a sintering furnace 40. The sintering temperature in the sintering furnace 40 is selected so that a sintered connection can be formed between the functional particles of the individual material components 8, 10, that is, in particular the metal particles composed of the alloy components, by a diffusion process. The sintering temperature is the temperature at which a local melting phase of the individual metal particles occurs, but the sintering temperature is lower than the melting temperature of the metal particles.
[0053] After the sintering process, the cooled magnet disc 2 is fed into a further processing process. Here, for example, the material depressions 16 can be introduced by a stamping process. The material elevations 20 can be introduced by a deformation process, so that the material depressions 16 are produced on one side of the magnet disc 2 and corresponding material elevations are formed on the other side.
[0054] It should be noted that the material concave lines 16 and the material ridges can also be already introduced into the green body 36. Here, the material ridges can be applied to the green body by other additive methods before the sintering process. For example, the material ridges can also be additionally sprayed or printed through a template.
[0055] Reference numerals list
[0056] 2 magnetic disks
[0057] 4 stacking groups
[0058] 6 Motor
[0059] 8. First Material Component
[0060] 10 Second Material Component
[0061] 12 Interface
[0062] 14Border Line
[0063] 16 Material groove
[0064] 18 Tangent
[0065] 20Material ridge line
[0066] 22 Central Axis
[0067] 24 rotors
[0068] 25 stator
[0069] 26 Shell
[0070] 28 side recess
[0071] 30 Templates
[0072] 32 Scraper
[0073] 34 Base material
[0074] 36 green
[0075] 38 Debonding furnace
[0076] 40 Sintering furnace
[0077] α extension angle
Claims
1. A rotationally symmetrical magnetic sheet (2) for additive manufacturing of a lamination stack (4) for an electric machine (6), wherein: There are at least two material components (8, 10) separated from each other in two-dimensional extension. - a first material component (8) and a second material component (10), wherein - the material components (8, 10) meet at an interface (12), said interface forming a boundary line (14) when viewed perpendicularly to the plane of the sheet, It is characterized in that - A material groove (16) is introduced into the magnetic sheet (2), the material groove extending from the first material component (8) through the boundary line (14) to the second material component (10), and the extension angle α of the material groove (16) relative to the tangent (18) of the boundary line (14) is 45° to 135°, and at the tangent, the material groove (16) intersects with the boundary line (14).
2. The magnetic sheet according to claim 1, characterized in that: A material ridge line (20) is introduced into the magnetic sheet (2), wherein the material ridge line extends from the first material component (8) through the boundary line (14) to the second material component (10), and the extension angle α' of the material ridge line relative to the tangent line (18) of the boundary line (14) is 45° to 135°, and at the tangent line, the material ridge line (20) intersects with the boundary line (14).
3. The magnetic sheet according to claim 1 or 2, characterized in that: The material grooves (16) have different depths.
4. The magnetic sheet according to any one of the preceding claims, characterized in that The length of the material groove (16) is 1 mm to 10 mm.
5. The magnetic sheet according to any one of the preceding claims, characterized in that The boundary line (14) is formed from one of the material components (8, 10) such that it forms an undercut in the other material component (8, 10).
6. The magnetic sheet according to any one of the preceding claims, characterized in that The extension of the boundary line (14) is designed to be rotationally symmetrical with respect to the center axis (22) of the magnetic disk (2).
7. The magnetic sheet according to any one of claims 1 to 6, wherein: The first material component (8) comprises a ferrous alloy having an austenitic structure of at least 25% by volume.
8. The magnetic sheet according to any one of claims 1 to 7, characterized in that: The second material component (10) comprises an iron alloy having at least 90% by weight, in particular at least 96% by weight, of iron.
9. The magnetic sheet according to claim 8, characterized in that: The second material component (10) has a ferrite or martensite structure.
10. The magnetic sheet according to any one of claims 1 to 9, characterized in that: The first material component (8) is a chromium-nickel alloy.
11. The magnetic sheet according to claim 10, characterized in that: The first material component (8) is an iron-chromium alloy having a chromium content of 22% to 28% by weight, in particular 24% to 26% by weight.
12. The magnetic sheet according to claim 9 or 11, characterized in that: The first material component (8) has a nickel content of between 4% by weight and 10% by weight, in particular between 6% by weight and 8% by weight.
13. A lamination stack for a rotor (24) of an electric machine (6), the lamination stack comprising a plurality of magnetic laminations (2) according to any one of claims 1 to 12.
14. The lamination stack according to claim 13, characterized in that: The magnetic sheets (2) are stacked in such a way that the material concave lines (16) of the first magnetic sheet (2) are filled with the material ridges (20) of the second magnetic sheet (2').
15. An electric machine comprising a lamination stack (4) according to claims 12 to 14.
Citation Information
Patent Citations
Method for sintering multicomponent sintering material, electric machine and electric vehicle
EP3629453A1
Method for producing a magnetic sheet and a magnetic sheet stack and electric machine and electric vehicle
EP3723249A1
Production of a metal object
EP3725435A1
Magnetic sheet, method for producing same, rotor and electrical machine
EP3932591A1